A review on coatings through thermal spraying - Qadir, Danial; Sharif, Rabia; Nasir, Rizwan; Awad, Ali; Mannan, Hafiz Abdul (Chemical papers, 2024)
Ceramic-coated metals with enhanced properties such as chemical and environmental deterioration resistance and high thermal stability have previously found widespread uses in various industries. However, their application was limited due to weak bonding at the interfaces of dissimilar materials. To achieve the necessary interfaces and bonding qualities, a variety of procedures, primarily mechanical treatments, were used. Interface structure and composition, transition temperature, and wettability are important characteristics. In this review, extensive study has been carried out for several thermal spray methods, such as flame spray, electric arc spray, and plasma spray technology. The study explores microstructural elements of plasma-sprayed coatings, including bonding mechanisms, pore creation, oxides formation, and other important process parameters. The study emphasizes how crucial wetness is to coating development. It looks at what affects wetting, how interfacial reactions affect reactive wetting, and how important additives or reactive materials are to encouraging wetting. In conclusion, the authors suggest the next studies and technological developments in coating technologies and thermal spray procedures. The study contributes to the continuous advancement of these processes and their applications by pointing out opportunities for more research and development.